Understanding professional development policies for novice lecturers: perspectives from the university management - Hong, Yu; Abdullah, Arnida; Muhamad, Mohd Mokhtar; Asimiran, Soaib (Human Resource Management Academic Research Society, 2023)
Professional development policy is an initiative intended to up-skill novice lecturers, and in so doing improve university education. This qualitative case study was conducted to explore the understanding of university management on professional development policies. Data were collected through in-depth interviews and documents. The participants were twelve university management at two selected public universities in China including vice-chancellors, directors of the Academic Affairs Office, deputy deans, and administrators in the Academic Affairs Office. Data from documents supplied the data obtained from interviews. Then, using thematic analysis to identify the themes that emerged from the data obtained. The findings of this study indicated that the university management has a comprehensive and deep understanding of professional development policies. As policymakers, they are aware of what the policy contains, which includes the policy target group, policy goals, guiding principles, and fields covered in policies. The university management should take and enact their role of lecturer professional development seriously, and provide useful activities and programs for novice lecturers to help them.